Administrative Work Evaluation In Public And Private Kindergartens (Journal of the College of Basic Education, 2026)
The current research aims to understand and compare administrative work in public and private schools. Therefore, the researcher developed an administrative work scale consisting of (25) items, which was then applied to the research sample. The researcher selected (80) female managers, 40 from government schools and 40 from private schools, then she re-extracted the validity and reliability coefficients for the scale. After this procedure, she entered the study data into the Statistical Package for the Social Sciences (SPSS) program, and the results showed the following:The research sample demonstrated successful administrative performance.The research sample exhibited an average level of administrative performance, particularly within the Riyadh Private Schools.There was a qualitative difference in administrative performance.